Arthroscopic Fractional Lengthening After Total Hip Arthroplasty Results in Improved Patient-Reported Outcomes and Low Rates of Revision Total Hip Arthroplasty - Karissa N. Simon, B.S.; Kevin Jurgensmeier, M.D.; Michael Vogel, B.S.; Michael J. Taunton, M.D.; Bruce A. Levy, M.D.; Shane J. Nho, M.D., M.S.; Mario Hevesi, M.D., Ph.D. (Arthroscopy, Sports Medicine, and Rehabilitation, 2024)
Purpose: To report the clinical outcomes and reoperation rates of arthroscopic and endoscopic iliopsoas release at short-term follow-up after ipsilateral total hip arthroplasty (THA) at 2 separate medical institutions and to evaluate whether demographic and radiographic parameters are associated with postoperative patient-reported outcomes (PROs). Methods: Patients with iliopsoas tendinitis in the setting of prior THA who underwent arthroscopic iliopsoas fractional lengthening from 1988 to 2023 at 2 academic institutions were reviewed. Patients were included if they had 12 months of follow-up and underwent evaluation of preoperative anterior acetabular component overhang, surgery satisfaction, postoperative subjective hip flexion strength and anterior groin pain improvement, modified Harris Hip Score, Single Assessment Numeric Evaluation score, Tegner activity scale score, visual analog scale (VAS) score, and revision hip arthroplasty. Results: Sixty hips in 58 patients (19 male and 39 female patients) were followed up for a mean of 39.3 months (range, 12.0-105.9 months) postoperatively. Of the patients, 77% reported feeling “much better” or “slightly better,” 75% reported improved anterior groin pain, and 60% reported improved subjective hip flexion strength. The surgery satisfaction rating was 7.2 ± 3.3 (scale of 0 to 10). The mean postoperative modified Harris Hip Score, VAS score for pain at rest, VAS score for pain with use, and Single Assessment Numeric Evaluation score were 73.9 ± 19.4, 1.3 ± 2.4, 3.8 ± 2.9, and 71.9 ± 21.9, respectively. Preoperative anterior acetabular component overhang was 3.3 ± 6.5 mm and did not significantly correlate with postoperative PROs (P ≥ .45). The Tegner score improved from 2.5 ± 1.7 preoperatively to 2.9 ± 1.4 postoperatively (P = .0253). Three patients underwent revision arthroplasty at a mean of 25.3 months (range, 11.6-40.4 months) postoperatively, with an acetabular component revision rate of 3.3%. Conclusions: Satisfactory outcomes and low revision arthroplasty rates were observed in patients undergoing arthroscopic iliopsoas lengthening after THA. There was no statistically significant relation between anterior acetabular component overhang and final PROs. Level of Evidence: Level IV, therapeutic case series.